Reconstruction of 3d video from 2d real-life sequences - Eduardo Ramos Diaz; Volodymyr Ponomaryov (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
In this paper, a novel method that permits to generate 3D video sequences using 2D real-life sequences is proposed. Reconstruction of 3D video sequence is realized using depth map computation and anaglyph synthesis. The depth map is formed employing the stereo matching technique based on global error energy minimization with smoothing functions. The anaglyph construction is implemented using the red component alignment interpolating the previously formed depth map. Additionally, the depth map transformation is realized in order to reduce the dynamic range of the disparity values, minimizing ghosting and enhancing color preservation. Several real-life color video sequences that contain different types of motions, such as translational, rotational, zoom and combination of previous ones are used demonstrating good visual performance of the proposed 3D video sequence reconstruction.